2023
DOI: 10.1002/jez.2726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of type 1 diabetes mellitus as a risk factor of Parkinson's disease in a Drosophila model

Abstract: Diabetes mellitus (DM) is a chronic metabolic disease characterized by high blood glucose levels, resulting from insulin dysregulation. Parkinson's disease (PD) is the most common neurodegenerative motor disorder caused by the selective loss of dopaminergic (DA) neurons in the substantia nigra pars compacta. DM and PD are both age‐associated diseases that are turning into epidemics worldwide. Previous studies have indicated that type 2 DM might be a risk factor of developing PD. However, scarce information abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This methodology represents an advancement over previous research methods, enhancing the reliability of the conclusions. A drosophila model of T1DM has shown reduced levels of tyrosine hydroxylase in the brain, a typical PD-related phenotype [ 8 ], suggesting that T1DM might be a risk factor for developing PD. On the other hand, compared to T1DM, T2MD model may be more associated with PD and has been demonstrated that more suitable for studying metabolic disturbance, which acts an early risk factor for PD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology represents an advancement over previous research methods, enhancing the reliability of the conclusions. A drosophila model of T1DM has shown reduced levels of tyrosine hydroxylase in the brain, a typical PD-related phenotype [ 8 ], suggesting that T1DM might be a risk factor for developing PD. On the other hand, compared to T1DM, T2MD model may be more associated with PD and has been demonstrated that more suitable for studying metabolic disturbance, which acts an early risk factor for PD [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…T1DM has been postulated to expedite cognitive decline [ 6 ],with reports of elevated levels of phosphorylated Tau protein in T1DM patients [ 7 ], a factor associated with increased intracellular neurofibrillary tangle (NFT) formation in AD [ 6 ]. Furthermore, prior research has suggested that T1DM might act as a predisposing factor for PD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Sanz et al [35] generated a Drosophila model of T1DM based on insulin deficiency and found that these flies displayed insulin deficiency, increased levels of carbohydrates and glycogen, and reduced activity of insulin signaling, which are features of T1DM. These flies developed motor defects, reduced tyrosine hydroxylase (seen in dopamine neurons), and increased oxidative stress in their brains, mirroring the pathophysiology of PD in humans.…”
Section: Discussionmentioning
confidence: 99%